trans-Difluoridotetrakis(pyridine-κN)chromium(III) perchlorate from synchrotron radiation - Moon, Dohyun (International Union of Crystallography, 2013)
The are two independent complex cations in the title salt, [CrF(2)(C(5)H(5)N)(4)]ClO(4), each located on a centre of inversion, as well as an independent perchlorate counter-ion. The complex cations adopt slightly distorted octahedral coordination environments around the Cr(III) ion, defined by four pyridine (py) N atoms in the equatorial plane and two F(−) ligands in the axial positions; intramolecular C—H⋯F contacts are noted. The mean Cr—N(py) and Cr—F bond lengths are 2.088 (6) and 1.8559 (10) Å, respectively. The three-dimensional architecture is sustained by hydrogen bonds involving the pyridine C—H groups as donors, and F and O atoms as acceptors.